MOSQUITO BEHAVIOR AND DENSITY FLUCTUATIONS Anopheles leucosphyrus group AS VECTOR KNOWLESI MALARIA IN IBOIH - Isfanda Isfanda; Fitria Fitria; Yuni Rahmayanti; Galih Ramadhan Sifa; Fitrah Rizqi Qaedi Papilaya (Universitas Islam Negeri Ar-Raniry, 2022)
Anopheles leucosphyrus group infected with the patogen Plasmodium knowlesi from Macaca fascicularis, Macaca nemestrina, and Macaca leonine. An. The leucosphyrus group consists of species An. crasens, An. latens, and An. introlotus. Anopheles mosquitoes have behavior and fluctuations in density at a punctual time in foraging and biting. This study used the Animal-baited trap net method, which is a method that uses farm animals as an attractant. Data collection that has been carried out, it was found that a mosquito An. leucosphyrus group has a dynamic behavior of biting from 08:00 PM to 03:00 AM, with the highest fluctuations occurring at 10:00 PM. The behavior and fluctuations of a mosquito An. leucosphyrus group varies during active biting in search of blood feed.